HUBUNGAN KERJASAMA ORANG TUA DAN GURU UNTUK MENDISIPLINKAN ANAK DI TK SE-KECAMATAN MEDAN TIMUR - Rika Dian Ervina Harahap; Anita Yus (JURNAL TEMATIK, 2019)
This study aims to knowing the relationship between parents and teachers todiscipline children in kindergartens throughout the East Medan sub-district. This researchis a descriptive correlational study. Data collection techniques through questionnaires andobservations. The population in this study were all kindergartens in the East Medan subdistrict which numbered 17 schools. The sample of this study amounted to 7 schoolsdetermined by simple random sampling. The data analysis technique uses productmoment correlation. The results achieved in the study are that there is a significantrelationship between cooperative relations and teachers to discipline children inkindergartens in the East Medan sub-district. The results of the product momentcorrelation between parent and teacher collaboration with child discipline are obtained bythe results of tcount > t table (3.05> 2.04), then the hypothesis testing is significant with Haresults accepted and H0 rejected.